Activation of Brain Attention Systems in Individuals with Symptoms of ADHD - P. Dennis Rodriguez; Gordon C. Baylis (Behavioural Neurology)
Previous research investigating attention and impulse control in individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) has largely ignored the symptomatic differences among the three subtypes of ADHD: ADHD-Inattentive Type, ADHD-Hyperactive/Impulsive Type, and ADHD-Combined Type. The present study examined attention and impulse control by focusing on these subtypes. Based on their self-reported symptoms of ADHD, participants belonged to one of four groups: ADHD-Inattentive, ADHD-Hyperactive/Impulsive, ADHD-Combined, and control. Cortical activity was recorded from participants during performance of a Go/NoGo task. The event-related potentials (ERP) measured at frontal and posterior sites discriminated between the control group and participants with symptoms of ADHD. The control group consistently exhibited a higher P3 amplitude than all the ADHD groups. The main difference occurred at the frontal site, indicating that individuals with ADHD symptoms have deficits in the anterior attentional system, which mediates signal detection. Behavioral measures of signal sensitivity revealed that the ADHD-Inattentive and the ADHD-Hyperactive/Impulsive groups had more difficulty with the attention-demanding Go/NoGo respond-to-target task, while behavioral measures of response bias indicated that the ADHD-Hyperactive/Impulsive and the ADHD-Combined groups responded more liberally in the inhibition-demanding Go/NoGo suppress-to-target task.